U‐Pb Detrital Zircon Analysis – Results of an Inter‐laboratory Comparison. Issue 3 (8th August 2013) - Košler, Jan; Sláma, Jiří; Belousova, Elena; Corfu, Fernando; Gehrels, George E.; Gerdes, Axel; Horstwood, Matthew S. A.; Sircombe, Keith N.; Sylvester, Paul J.; Tiepolo, Massimo; Whitehouse, Martin J.; Woodhead, Jon D.
Abstract : Inter‐laboratory comparison of laser ablation ICP‐MS and SIMS U‐Pb dating of synthetic detrital zircon samples provides an insight into the state‐of‐the art of sedimentary provenance studies. Here, we report results obtained from ten laboratories that routinely perform this type of work. The achieved level of bias was mostly within ± 2% relative to the ID‐TIMS U‐Pb ages of zircons in the detrital sample, and the variation is likely to be attributed to variable Pb/U elemental fractionation due to zircon matrix differences between the samples and the reference materials used for standardisation. It has been determined that 5% age difference between adjacent age peaks is currently at the limit of what can be routinely resolved by the in situ dating of detrital zircon samples. Precision of individual zircon age determination mostly reflects the data reduction and procedures of measurement uncertainty propagation, and it is largely independent of the instrumentation, analytical technique and reference samples used for standardisation. All laboratories showed a bias towards selection of larger zircon grains for analysis. The experiment confirms the previously published estimates of the minimum number of grains that have to be analysed in order to detect minor zircon age populations in detrital samples.